Rue Des Martyrs retreat (Architecture Image Studies, 2020)
Slowly, from left to right, I inscribe a sharp but almost imperceptible pencil line across the surface of the paper, with the aid of a metal ruler. I always draw this horizontal line in exactly the same relation to the bottom of the page, so as to replicate the same procedure enacted upon all previous drawings. Unfortunately, I often find that each page has not been cut quite square, so the next line, a vertical one, is drawn with the aid of a set square, with which I apply two guiding pencil marks. I then take up the metal ruler again and draw a fine pencil line between these two points. Upon the page are now two lines crossing to form an off-centre axis, which inhabit the lower right-hand part of the page.